Curriculum Evaluation Model in Development Higher Education Curriculum - Rifky Serva Tuju; George Rumbekwan; Donna Crosnoy Sinaga; Vonny Ellss; Yehuda Mandacan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The curriculum evaluation model decides the direction in the evaluation process. The curriculum cannot be separated from the evaluation process. Evaluation provides progress and has an impact on the emergence of curriculum strengths and weaknesses. So that the evaluation can provide clarity and can be seen where the weaknesses and strengths of the curriculum. In evaluating the curriculum, it cannot be separated from what evaluation model is chosen in conducting the evaluation. Aspects such as the purpose, function, form, and model of curriculum evaluation become an important part in a curriculum evaluation and become a reference in evaluating curriculum development in higher education.